Is There is a Correlation between Vitamin D Status and Glycemic Control (HBa1c) in Patients with Type 2 Diabetes Mellitus: Review Article with Meta-Analysis - Ali Shlash Al- Ibrahimy (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background and Purpose: Diabetes mellitus type 2 represent significant problem for health care givers because of its huge prevalence.The clue for non-skeletal impact of vitamin D become increasing suggesting the potential benefit in many diseases related to cardiac system, immunity disorders and diabetes mellitus type 2.We achieved this systematic review containing cross-sectional studies to assess the association between vitamin D status glycaemiaindex as represented by glycosylated hemoglobin.Method: We achieved literature search for cross-sectional studies which consider the impact of status of vitamin D on HBa1c as major outcome of interest. The author targets database like Medline and google scholar database for cross-sectional trials for period up to December 2020. The software utilized to analyze the data statistically was comprehensive meta-analysis (CMA).Results: Eighteen clinical trials have been identified by search.Thirteen studies found the inverse correlation between glycemic index (HBa1c) and patient’s status of vitamin D.It was founded that the overall combined influence of vitamin D level on glycosylated hemoglobinwas significant (p = 0.001, and 95% CI: - 0.230 to -3.268).Conclusion: The current review revealed that the impact of status of vitamin D in correction of glycaemia was significant. Thepatient’s vitamin D status can has important impact on the pathogenesis of T2DM. The diabetic patients with poor indices of glycaemia has higher prevalence of decreased vitamin D level referring to potential benefit of vitamin D in correction of such indices.